Awareness on Air Pollution and Risk Preparedness among Residents in Kigali City of Rwanda - Nahayo, Lamek; Nibagwire, Deborah; Habiyaremye, Gabriel; Kalisa, Egide; Udahogora, Madeleine; Maniragaba, Abias (International Journal of Sustainable Development & World Policy, 2019)
The rapid human population growth, industrialization, urbanization, agricultural expansion and other development activities are gradually polluting the quality of air with severe effects on the human health and environment as well. This is particularly, exacerbated by lack information sharing which limits the risk assessment, and community approach to identify the key sources and the mitigation or adaptation strategies. The aim of this study was to assess the extent of air pollution risk awareness in order to enhance its preparedness and adaptation in Kigali City of Rwanda. The authors conducted an interview with 225 respondents randomly selected among the residents in May 2018. The results indicated that the primary air pollution sources are automobile highlighted by 45 percent of respondents, followed by stationery sources at 36 percent. However, the air pollution risk related information is mainly provided at television (50%), owned by 32 percent in contrast of radio possessed by 49% of residents, but used at low extent (36%). This consequently, leads to health problems, acid rain and natural resources depletion as stated by the informants. Accordingly, the air pollution risk awareness is at low level, as respondents highlighted that the related education/training is delivered at low extent (9.3 percent), despite its role in risk awareness and preparedness among the community. While the car free day (32.4%) and forestland expansion (42%) are practiced at large extent than education. The relevant community air pollution risk awareness and reduction measures are suggested.